Preliminary study on phytogeography of Dipterocarpaceae Blume family in Vietnam - Tai, Vu Anh; Vinh, Pham The; Van, Tran Thi Thuy; Thoa, Le Thi Kim; Hoang, Le Duc; Hong, Ngo Thi Bich (Vietnam Journal of Earth Sciences, 2017)
Biogeographically mapping flora of Vietnam requires the studies on the distribution of some important species groups for identifying the typical species composition of each phytochorion. The Dipterocarpaceae family contains taxa originated in tropical Asia and its subfamily of Dipterocarpoideae is proved to have Southeast Asia origin. In Vietnam, this family includes 43 species in 7 genera. In this study, Dipterocarpaceae species from 645 sites in Vietnam are assessed and compared to those in over the world. In Vietnam, this family distributes in tropical and/or slightly passing to subtropical climate but none of its species is naturally found in the Red River and the Mekong River deltas. In the world, the Dipterocarpaceae species found in Vietnam concentrated distributes in Indochina floristic region, corresponding to the originative area of South Myanmar. Statistically, there are 12 endemic species for the Indochinese floristic region and five of them are endemic for four provinces of this region related to Vietnam, respectively as follows: South China - 1, North Indochina - 1, South Indochina - 2 and Annam - 1. Additionally, some species distribute in East Asia floristic region of Holarctic Kingdom because of expanding the distribution area from the Indochinese floristic region. All genera of this family in Vietnam were originated in the Indochinese floristic region. Moreover, the floristic data and phytogeographical phylogeny diagram, based on analyses of phytogeography and DNA, would be better to use for finding out the distributional source or the forming time of species or genus, then the phylogenetic diagram. References Angiosperm Phylogeny Group, 2009. An update of the Angiosperm Phylogeny Group classification for the orders and families of flowering plants: APG III. Botanical Journal of the Linnean Society, 161(2), 105-121. Ashton P.S., 1982. Dipterocarpaceae. In: Van Steenis C.G.G.J., 1979-1983, Flora Malesiana. Dipterocarpaceae. Martinus Nijhoff Publisher, The Hague, London, 9(2), 250p. Averyanov L.V., Phan K.L., Nguyen T.H., Harder D.K., 2003. Phytogeographic review of Vietnam and adjacent areas of Eastern Indochina, Komarovia, Saint Petersburg, 3, 1-83. Kress W.J., DeFilipps R.A., Farr E. and Yin D.Y.K., 2003. A checklist of the trees, shrubs, herbs and climbers of Myanmar. National Museum of Nature History, Washington DC, 45, 1-590. Le Tran Chan (Editor), 1999. Some characteristics of the flora of Vietnam. Science and Technique publishing house, Hanoi, 305p (Vietnamese). Li X.W., Li J., Ashton P.S., 2007. Dipterocarpaceae. In: Wu Z.Y., Raven P.H. (Hrsg.). Flora of China. Missouri Botanical Garden Press, St. Louis, 13, 48-54. Nguyen Hoang Nghia, 2005. Dipterocarps of Vietnam. Agriculture Publishing House, Hanoi, 100p. Nguyen Kim Dao, 2003. “Dipterocarpceae Blume, 1825” in Checklist Plant species of Vietnam. Agricultural Publishing House, Hanoi, 2, 328-340 (Vietnamese). Nguyen Nga Phi, 2009. Molecular phylogeny of Southeast-Asian Dipterocarps belonging to tribe Dipterocarpeae (family Dipterocarpaceae) based on non-coding sequence data of chloroplast and nuclear DNA. Department of Forest Genetics and Georest Tree Breeding, Büsgen Institute, Faculty of Forest Science and Forest Ecology, Georg-August University of Göttingen. Göttingen, 142p. Nguyen Nghia Thin, 2004. Methods in Botanical Research. HNU publishing house, Hanoi, 172p (Vietnamese). Pham Hoang Ho, 2001. Illustration Flora of Vietnam, Youth Publishing House. Ho Chi Minh City, 2, 1022p (Vietnamese). Smitinand T., 1969. The distribution of Dipterocarpaceae in Thailand. National History Bull. Siam Soci., 23, 67-75. Smitinand T., J.E. Vidal, P.H. Ho, 1990. Flore du Cambodge, du Laos et du Vietnam, 25, Diptérocarpacées. Muséum National d’Histoire Naturelle, Paris, 123p (French). Takhtajan A. (Translated by Theodore J. Crovello), 1986. Floristic Regions of the World. University of California Press, 544p. Thai Van Trung, 1978. Tropical Forest Ecology systems of Vietnam. Science and Technique publishing house, Hanoi, 314p (Vietnamese). The Plant List (Version 1.1.), 2013. Dipterocarpaceae. http://www.theplantlist.org.